2012
DOI: 10.1016/j.crohns.2011.11.010
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism in UGT1A1 related to hyperbilirubinemia is associated with a decreased risk for Crohn's disease

Abstract: The homozygous state of the UGT1A1*28 polymorphism, associated with higher serum bilirubin levels, may be protective for the development of Crohn's disease, suggesting that the anti-oxidant capacity of bilirubin may play a part.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 45 publications
1
22
0
4
Order By: Relevance
“…Jaundiced patients with concomitant ulcerative colitis and PSC seem to manifest milder or asymptomatic colitis when compared with patients with normal bilirubin levels (10). Similarly, patients with Gilbert syndrome, who have higher levels of UCB because of defective UDP glucuronosyl transferase 1 (UGT1A1), are less likely to develop IBD, further supporting the immunoprotective role of UCB in this condition (11,12). Gunn rats with pronounced defects in UGTA1, an experimental model of Crigler-Najjar syndrome, are likewise relatively resistant to induction of experimental colitis (13).…”
Section: Introductionmentioning
confidence: 96%
“…Jaundiced patients with concomitant ulcerative colitis and PSC seem to manifest milder or asymptomatic colitis when compared with patients with normal bilirubin levels (10). Similarly, patients with Gilbert syndrome, who have higher levels of UCB because of defective UDP glucuronosyl transferase 1 (UGT1A1), are less likely to develop IBD, further supporting the immunoprotective role of UCB in this condition (11,12). Gunn rats with pronounced defects in UGTA1, an experimental model of Crigler-Najjar syndrome, are likewise relatively resistant to induction of experimental colitis (13).…”
Section: Introductionmentioning
confidence: 96%
“…Bilirubin has potent anti-oxidant activity by scavenging ROS molecules [24e27]. It also shows anti-inflammatory capability in multiple sclerosis [28], asthma [29], Crohn's disease [30], allergic pneumonitis [31], and autoimmune encephalomyelitis [32]. Based on these cytoprotective effects of bilirubin, previous studies revealed that treatment with bilirubin could not only protect islet cells against oxidative damage during the isolation process, but also induce tolerance to islet cells in syngeneic or allogeneic transplantation [33e35].…”
Section: Introductionmentioning
confidence: 99%
“…Однак останнім часом отримані дані, що пере-конливо свідчать про гетерогенність СЖ, оскільки у хворих із цим захворюванням є ознаки порушен-ня практично всіх етапів обміну білірубіну -від його продукції до виведення з організму [16]:…”
Section: ключові слова: синдром жильбера; гіпербілірубінемія; уридиндunclassified